Influenza virus damages the alveolar barrier by disrupting epithelial cell tight junctions - Short, Kirsty R.; Kasper, Jennifer; van der Aa, Stijn; Andeweg, Arno C.; Zaaraoui-Boutahar, Fatiha; Goeijenbier, Marco; Richard, Mathilde; Herold, Susanne; Becker, Christin; Scott, Dana P.; Limpens, Ronald W.A.L.; Koster, Abraham J.; et al. (The European respiratory journal, 2016)
A major cause of respiratory failure during influenza A virus (IAV) infection is damage to the epithelial–endothelial barrier of the pulmonary alveolus. Damage to this barrier results in flooding of the alveolar lumen with proteinaceous oedema fluid, erythrocytes and inflammatory cells. To date, the exact roles of pulmonary epithelial and endothelial cells in this process remain unclear. Here, we used an in vitro co-culture model to understand how IAV damages the pulmonary epithelial–endothelial barrier. Human epithelial cells were seeded on the upper half of a transwell membrane while human endothelial cells were seeded on the lower half. These cells were then grown in co-culture and IAV was added to the upper chamber. We showed that the addition of IAV (H1N1 and H5N1 subtypes) resulted in significant barrier damage. Interestingly, we found that, while endothelial cells mounted a pro-inflammatory/pro-coagulant response to a viral infection in the adjacent epithelial cells, damage to the alveolar epithelial–endothelial barrier occurred independently of endothelial cells. Rather, barrier damage was associated with disruption of tight junctions amongst epithelial cells, and specifically with loss of tight junction protein claudin-4. Taken together, these data suggest that maintaining epithelial cell integrity is key in reducing pulmonary oedema during IAV infection.